Abiotic Methane Generation via CO2 Hydrogenation With Natural Chromitite Under Hydrothermal Conditions. (6th April 2021) - Ueda, Hisahiro; Matsui, Yohei; Sawaki, Yusuke
Abstract: In modern continental serpentinization systems and ultramafic rock‐hosted sub‐seafloor hydrothermal systems, it is believed that chromitite plays an important role in abiotic hydrocarbon generation. Previous experiments have suggested that chromite acts as a catalyst of CH4 generation, but the composition of chromite used in the previous experiment is unrealistic on Earth. On the other hand, other studies have suggested that natural chromite including Mg and Al cannot function as a catalyst for CH4 generation. Consequently, it still remains uncertain whether naturally occurring Cr‐rich minerals promote CH4 generation. We monitored the reaction between naturally occurring chromitite and CO2 ‐rich fluid at 300°C, 500 bars. We performed two experiments in different initial CO2 /H2 ratios. In both experiments, CH4 was generated immediately after the beginning of experiments. When CO2 was more abundant than H2, the CH4 concentration in the fluid decreased below the detection limit value. On the other hand, when H2 was more abundant than CO2, the CH4 concentration in the fluid was maintained above 0.01 mmol/kg. This is the first report to demonstrate that naturally occurring Cr‐rich minerals act as a promotor of CH4 generation. Cr‐rich minerals such as Cr spinel are common accessory mineral in ultramafic rock. Therefore, on the early Earth, a certain level (on the order of 0.01 mmol/kg) of CH4 was likely produced through reactions between ultramafic rock and CO2 ‐bearing fluid. To produce more abundant CH4, more favorable conditions featuring greater quantities of Cr spinel and much higher H2 concentration (H2 /CO2 ratio) must be necessary. Key Points: Naturally occurring Cr‐rich minerals act as a promotor of CH4 generation High H2 /CO2 ratio in the fluid is favorable to sufficiently reduce CO2 to CH4 H2 ‐rich fluid could be needed to sustain methanotrophic community on the early Earth